JOOSTE, S.J.J. Inventory of documents - JOOSTE, S.J.J. (ARCA, 2018)
Minute book NP - transferred to PV 27, NP Cape collection, file 1
COVERAGE: 1940-1966
Keywords: JOOSTE, S.J.J.; Inventories; Politicians; National Party